The Spirit of the Nakaz : Catherine II’s Literary Debt to Montesquieu - Jones, W. G. (1998)
The Spirit of the Nakaz : Catherine II’s Literary Debt to Montesquieu (1998) 10 juin 2012, par Jones, W. G. Slavonic and East European Review, 76, 4, octobre 1998, p. 658-671.
Keywords: exportSPIP